Effect of Spin‐Crossover‐Induced Pore Contraction on CO2–Host Interactions in the Porous Coordination Polymers [Fe(pyrazine)M(CN)4] (M = Ni, Pt). Issue 4 (5th December 2012) - Culp, Jeffrey T.; Chen, De‐Li; Liu, Jinchen; Chirdon, Danielle; Kauffman, Kristi; Goodman, Angela; Johnson, J. Karl
Abstract: Variable‐temperature in situ ATR‐FTIR spectra are presented for the porous spin‐crossover compounds [Fe(pyrazine)Ni(CN)4 ] and [Fe(pyrazine)Pt(CN)4 ] under CO2 pressures of up to 8 bar. Significant shifts in the ν3 and ν2 IR absorption bands of adsorbed CO2 are observed as the host materials undergo transition between low‐ and high‐spin states. Computational models used to determine the packing arrangement of CO2 within the pore structures show a preferred orientation of one of the adsorbed CO2 molecules with close O=C=O··· H contacts with the pyrazine pillar ligands. The interaction is a consequence of the commensurate distance of the inter‐pyrazine separations and the length of the CO2 molecule, which allows the adsorbed CO2 to effectively bridge the pyrazine pillars in the structure. The models were used to assign the distinct shifts in the IR absorption bands of the adsorbed CO2 that arise from changes in the O=C=O··· H contacts that strengthen and weaken in correlation with changes in the Fe–N bond lengths as the spin state of Fe changes. The results indicate that spin‐crossover compounds can function as a unique type of flexible sorbent in which the pore contractions associated with spin transition can affect the strength of CO2 –host interactions. Abstract : Modeling results confirm that the pore widths of the pillared Hofmann compounds [Fe(pyrazine)M(CN)4 ] are a good fit for adsorbed CO2, which spans the perpendicular distance between pyrazine pillar ligands through a four‐fold hydrogen‐bonding arrangement. Analysis shows how pore contraction resulting from a shortening of the Fe–N bonds during spin crossover enhances these H··· O interactions.